Pelaksanaan Pembelajaran Pianika Pada Pembelajaran Seni Budaya Menggunakan Whatsapp Grup Di Kelas VII-1 SMP Negeri 40 Padang - Axlvaridzi Chandra Dyta; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2020)
This study aims to reveal how melodicalearning using online system in grade VII of SMP Negeri 40 Padang is conducted. It includes planning, implementation, and evaluation in the COVID-19 pandemic situation. The theory used in this study is learning and instruction theory. This research belongs to a qualitative research with descriptive analytic approach. The data were collected through observation, interviews, and literature study. The data analysis was conductedthrough identification, classification, clarification, analysis, explanation, and conclusion. The results show that learning process of Culture and Arts subject at SMP Negeri 40 Padang is conductedfrom home through online learning. Due to learning situation and condition, the teacher designs instructionwhich is is relatively different from face-to-face learning in classrooms.The planning step done by the teacher is preparing learning materials and sending them to students via WA. The materials consist of messages, subject matter, learning activities, and obligations students have to fulfill.The learning implementation conducted by the teacher is controlling student learning by askingthem to send a video recording of blowing, fingering, and training for the BungoParawitan song.Almost all students send video recordings on time. Some of them do not send the videos on time, and these are evaluation and barriers ofonline learning of melodica. The results of grade VIIstudents’ learning outcomes at SMP Negeri 40 Padang are good. The obstacles faced by the teacher in its implementation are related to preparation, presentation, practice, and the performanceof learning outcomeswhich are very inadequate.